Comparative Analysis of Financial Performance Before and During the Covid-19 Pandemic at BTPN Syariah - Desmy Riani; Denia Maulani; Dewi Megawati; Hannisa Rahmaniar; Puspita Sari; NA Rumiasih (Universitas Serang Raya, 2022)
This research aims to see the financial performance of BTPN Syariah before and after the COVID-19 pandemic as measured by profitability and liquidity ratios. The method used in this research is the quantitative data method, the type of data used is secondary data. By using financial data sourced from the balance sheet and profit and loss statements of BTPN Syariah in 2016-2020. This study uses a descriptive analysis method with a quantitative approach. Based on the results of research on financial performance as measured by profitability ratios with indicators of ROA, there was decrease before and after covid by 5.03 percent, which was caused by decrease in profit. The BOPO ratio there was decrease before and after covid by 6.35 percent, which was caused by decrease in operating income. However, ROA and BOPO are still in very healthy categorization, both before the pandemic and after the pandemic. In the NOM ratio, the performance before pandemic in less healthy category and after pandemic there was decrease by 0.39 percent to be unhealthy which cause by decrease in net operating income. The ROE ratio before the pandemic was in very healthy condition, after the pandemic there is decrease by 11.89 percent to be healthy enough. Then the measurement of financial performance using the liquidity ratio by the FDR parameter, financial performance both before and during the pandemic was in quite a Healthy condition. In the ratio of NPF, FAR, and Quick Ratio, the performance before and after the pandemic was in very healthy condition.